Agricultural Research Practices through a Local Lens: Adapting the Ithaka S + R Study for Your Campus. Issue 1 (2nd January 2019) - Hendrix, Beth R.
Abstract: How do the research practices and challenges of agriculture scholars at the University of Idaho (U of I) contrast with those of their peers at other land grant universities? To answer that question, this paper compares qualitative data from U of I researchers to findings from a nationwide study of agricultural research practices. Because the U of I did not participate in the nationwide study, this local study provides a framework for identifying issues that are unique to researchers within our local context. Furthermore, the paper demonstrates how a similar methodology can be used by library liaisons to better understand the challenges of researchers in any discipline and help determine which new and existing research support services best meet their needs.